Effects of circular myotomy on the healing of esophageal suture anastomosis: an experimental study - Tannuri,Uenis (1999)
For esophageal reconstruction in newborns with esophageal atresia, esophageal reunion with an end-to-end anastomosis is the ideal procedure, although it may result in leaks and strictures due to tension on the suture line, mainly in cases with a wide gap between the ends. Circular myotomy (Livaditis' procedure) is the best method to elongate the proximal esophageal pouch and reduce anastomotic tension. This experimental investigation in dogs was undertaken to attempt to verify that circular myotomy decreases the anastomotic leak rate in newborns with wide gap esophageal atresia, and to analyze whether the technique promotes morphologic changes in the anastomotic scar. A pilot study demonstrated that it is necessary to resect more than 8 cm (40% of the total esophageal length) in order to obtain high leak rates. In the experimental project, such resection was performed in dogs divided into two groups (control group, anastomosis only, and experimental group, anastomosis plus circular myotomy in the proximal esophageal segment). The animals were killed in the 14th postoperative day, submitted to autopsy, and were evaluated as to the presence of leaks and strictures, as well as to the features (macroscopic and microscopic aspects) of the anastomosis. Leak rates were the same in both groups. Morphometric analysis revealed that in animals in the experimental group, the anastomotic scar was thinner than the control animals, and the isolated muscular manchette distal to the site of myotomy was replaced by fibrous tissue. Correspondingly, a decreased number of newly formed small vessels were noted in the experimental animals, compared to control animals. We concluded that circular myotomy does not decrease the incidence of anastomotic leaks, and it also promotes deleterious changes in anastomotic healing.